2016
DOI: 10.1016/j.exphem.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis and comparison of two bone marrow stromal cell lines using the SILAC method

Abstract: Two human bone marrow stromal cell lines, HS5 and HS27a, co-cultured with myeloid cells, have frequently been used in studies of cross talk between cells in the bone marrow microenvironment and hematopoietic cells. Altered expression of proteins is typically associated with cell-cell signal transduction and regulation of cellular functions. Many studies have focused on key proteins that contribute to functional differences in cell co-culture models, but global quantitative proteome analysis of HS5 and HS27a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Based on our in vitro observations, we intravenously co-injected HS5 cells and MDS marrow-derived hematopoietic cells into Nod.cg-Prkdc scid Il2rg tm1wjll (NSG) mice, and observed that differential stromal contact had structural and functional effects on proliferation of MDS precursor cells [40]. Also, we used glycomics (lectin microarray) and proteomics (SILAC method) approaches to compare two bone marrow stromal cell lines, HS5 and HS27a, and observed differential expression of several glycans and proteins [18, 41]. These and many similar findings indicate that microenvironmental factors play key roles in both normal and pathological hematopoiesis, and that hematopoiesis is modulated by bidirectional signals between hematopoietic cells and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our in vitro observations, we intravenously co-injected HS5 cells and MDS marrow-derived hematopoietic cells into Nod.cg-Prkdc scid Il2rg tm1wjll (NSG) mice, and observed that differential stromal contact had structural and functional effects on proliferation of MDS precursor cells [40]. Also, we used glycomics (lectin microarray) and proteomics (SILAC method) approaches to compare two bone marrow stromal cell lines, HS5 and HS27a, and observed differential expression of several glycans and proteins [18, 41]. These and many similar findings indicate that microenvironmental factors play key roles in both normal and pathological hematopoiesis, and that hematopoiesis is modulated by bidirectional signals between hematopoietic cells and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…HS27a supports “cobblestone area” formation by early hematopoietic progenitor cells, whereas HS5 secretes multiple cytokines that support proliferation of committed progenitor cells [17]. In our previous studies, we integrated information on quantitative proteomic data with genomic data to discover several differentially expressed proteins in two bone marrow stromal cells HS5 and HS27a [18]. The SILAC method has many advantages to reduce sample to sample variability therefore is highly suitable for protein quantification [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…KG1a cells (derived from acute myeloid leukemia) and bone marrow-derived stromal cell line HS27A are generous gifts from Professor H. Joachim Deeg (Fred-Hutchinson Cancer Research Center, Seattle, WA, USA). KG1a and HS27A were grown, propagated and subjected to experiments between passages 8 and 24, as previously described (27). Multiple aliquots from early passages were cryopreserved for later use.…”
Section: Methodsmentioning
confidence: 99%
“…The secretory pattern of tumor cells and their neighboring stromal cells is dynamically changed in tumor microenvironment. The secreted proteins are often present with high numbers and low abundance, and interfered by serum proteins in culture medium and contaminations of intracellular proteins released by cell lysis during sample preparation 7 9 . In order to sensitively detect active cell-cell interactions mediated by secreted proteins in tumor microenvironment, the SILAC (stable isotope labeling of amino acids in cell culture) based quantitative proteomic strategy showed us the good confidence due to its sensitivity and accuracy 6 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to sensitively detect active cell-cell interactions mediated by secreted proteins in tumor microenvironment, the SILAC (stable isotope labeling of amino acids in cell culture) based quantitative proteomic strategy showed us the good confidence due to its sensitivity and accuracy 6 , 10 . The SILAC-combined mass spectrometry (MS) has been widely used in varied studies, including screening disease biomarkers 9 13 , drug targets 14 16 , monitoring changes in post-translational modifications 17 19 and finding key factors in the complex signal pathway 10 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%